Studi Identifikasi Faktor-Faktor yang Mempengaruhi Prokrastinasi Akademik pada Siswa di SMP Negeri 1 Pasaributobing Kabupaten Tapanuli Tengah - Olmade Putri Bondar; Endang Haryati (Jouska: Jurnal Ilmiah Psikologi, 2023)
This article aims to determine how much the factors that influence academic procrastination in students at SMP Negeri 1 Pasaributobing, Kabupaten Tapanuli Tengah. The method used in this research is a descriptive quantitative approach. The sample in this study was class VIII Students in the 2021/2022 academic year, with a total sample of 60 students. The sampling technique used was total sampling technique. With the research scale using the Likert scale method. The data analysis technique used is descriptive statistical analysis (F % or percentage of factors). Based on the results of data analysis, it is known that the percentage of factors that contribute to influencing academic procrastination in students at SMP Negeri 1 Pasaributobing, which includes internal factors consisting of physical condition factor by 26%, and psychological condition factor by 24%. While external factors consist of parenting style factor by 25%, and environmental condition factor by 25%. So with that is concluded that the highest factors that contributes to influence academic procrastination in students is an internal factor with an indicator of physical condition factor that is 26%, anda the lowest factor is also in internal factors, with indicator psychological condition factor by 24%. Meanwhile, external factors which consist of parenting style factor and environmental condition have the same percentage.